SISTEM INFORMASI AKUNTANSI TENTANG PERSEDIAAN PRODUK JADI DI CV. BOLU KETAN MENDUT WARU SIDOARJO - Riska Imtikhalun Nafifah; Rika Yuliastanti (Ekomania, 2023)
Small Companies or Micro, Small and Medium Enterprises (MSMEs) are the supporters of the country's economy to progress. Not only has a role in economic development and opening up jobs, this sector has a role in the distribution of development producers. MSMEs have an important role in developing business in Indonesia. The growth of large businesses starts from SMEs. Therefore, MSMEs must always be developed and active so that they can continue to advance and compete with other, larger companies. The existence of an MSME accounting information system can be a method of preparing various kinds of reports needed by MSMEs. The author's activities in this study have the aim of understanding how the procedure for recording finished product inventory in the warehouse and to provide knowledge on how to use the Accounting Information System (AIS) in the company CV. Mendut Sticky Sponge. CV. Bolu Ketan Mendut is an example of UMKM in Sidoarjo which is in the trading industry in the form of pastries called Keripik Brownis Ketan. This research is a qualitative research using a descriptive approach, qualitative analysis data has been collected in various ways such as observation, interviews and documentation. The results of this study indicate that CV. Bolu Ketan Mendut has implemented a good and correct Standard Operating Procedure (SOP).